Efficacy and Safety of Eldecalcitol for Osteoporosis: A Meta-Analysis of Randomized Controlled Trials - Liu, Hongyan; Wang, Guoqi; Wu, Ting; Mu, Yiming; Gu, Weijun (Frontiers in Endocrinology, 2022)
Object: Eldecalcitol (ED-71) is a new vitamin D analog considered as the first-line drug for osteoporosis. However, inconsistent results have been reported in this regard. Hence, this meta-analysis of randomized controlled trials (RCTs) aimed to assess the efficacy and safety of ED-71 for osteoporosis. Methods: The PubMed, Embase, and the Cochrane Library databases were systematically searched to identify potential trials from inception until April 2021. The investigated outcomes included bone mineral density and fractures at various sites, and potential adverse events. The pooled effect estimates were calculated using weighted mean difference (WMD) and relative risk (RR) with 95% confidence interval (CI) using the random-effects model. Results: Eight RCTs involving 2368 patients were selected for the final meta-analysis. The pooled results showed that ED-71 were associated with a higher level of femoral neck (FN) bone mineral density (BMD) (WMD: 0.92; 95% CI: 0.24–1.60; P = 0.008), while it had no significant effect on lumbar spine BMD (WMD: 1.09; 95% CI: –0.11 to 2.30; P = 0.076) and hip BMD (WMD: 1.12; 95% CI: –0.16 to 2.40; P = 0.088). Moreover, the use of ED-71 could protect against the risk of all osteoporotic fracture (RR: 0.70; 95% CI: 0.55–0.88; P = 0.003) and vertebral fracture (RR: 0.74; 95% CI: 0.55–0.98; P = 0.038), while it did not affect the risk of nonvertebral fracture (RR: 0.53; 95%CI: 0.23–1.23; P = 0.140). The subgroup analyses found that the effects of ED-71 were superior to those of alfacalcidol on both BMD and fracture results. Moreover, the use of ED-71 plus bisphosphonate was associated with a greater improvement in BMD at various sites compared with bisphosphonate alone. Finally, ED-71 was associated with an increased risk of increased urine calcium level (RR: 1.69; 95% CI: 1.33–2.15; P < 0.001). Conclusion: This study found that the use of ED-71 could improve BMD and fractures at various sites, especially compared with alfacalcidol or a combination with bisphosphonate for patients with osteoporosis.